The role of optical coherence tomography in post cataract surgery macular edema in diabetic patients - Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Macular edema is one of the most common causes of visual impairment after uncomplicated cataract surgery nowadays. Its reported incidence ranges between 1% and 30%, with clinically significant post cataract macular edema occurring in patients with no risk factors at the incidence of 0.1% to 2.3%. The pathophysiology of post cataract macular edema remains uncertain and many various factors have been implicated in its development, including inflammation, vascular permeability, vitreo-macular tractions and light toxicity. A higher incidence of post cataract macular edema has been reported to occur in eyes with diabetic retinopathy and in eyes with preexisting diabetic macular edema, as worsening of macular edema has been observed after cataract surgery. Diabetes increases the risk of post cataract macular edema 1.8-fold and the diabetic retinopathy increases the risk of this complication 6.2-fold. Macular edema can be detected during clinical examination, angiography or optical coherence tomography. Of the three techniques, optical coherence tomography has the highest sensitivity, allowing to obtain qualitative and quantitative parameters of macula and to explore structural spatial relationships before and after cataract surgery in diabetic patients.